PENGARUH CAREER COMPETENCIES DAN PSYCHOLOGICAL CAPITAL TERHADAP SUBJECTIVE CAREER SUCCESS YANG DIMEDIASI OLEH JOB CRAFTING PADA PEGAWAI KANTOR BAPPEDA ACEH - Quddusisara Quddusisara; Lenny Rakhmawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2022)
This study aims to measure the effect of career competencies and psychological capital on subjective career success mediated by job crafting for employee at the Aceh Bappeda Office. The sample used in this study were employee of the Aceh Bappeda Office, totaling 87 people. The data collection equipment used in this study was a questionnaire. The sampling technique used is Saturated Sample. The data analysis method used is Statistical Product and Service Solutions (SPSS). The conclusion of the hypothesis test shows that career competencies have a positive effect on subjective career success, psychological capital has a positive effect on subjective career success, career competencies have a positive effect on job crafting, psychological capital has a positive effect on job crafting, job crafting has a positive effect on subjective career success, job crafting mediates the effect of career competencies on subjective career success, job crafting mediates the effect of psychological capital on subjective career success.